The Two Covenants: An Interpretation of the 4Q158 Fragments. (March 2019) - Werman, Cana
The underlying assumption of this article is that fragments 1–4 and 14 of 4Q158 represent an independent composition, not related to fragments 5–12 of 4Q158, where Exodus 19–22 in its proto-Samaritan version is copied. Identification of a common denominator for fragments 1–4 and 14 (labelled here as 4Q158b) is the main task of this article. This study shows that 4Q158b expresses a particular exegetical understanding of the biblical covenants and that its author's intentions and exegetical processes are best clarified in light of the book of Jubilees. According to Jubilees, two covenants were made by God at the creation of the world: one with humanity and another with the people of Israel. 4Q158b collects biblical passages (Gen. 31–32; Exod. 3–4; Exod. 24) in which it discerns hints of various expressions of commitment to these two covenants between the period of Abraham and the events at Sinai. The author of the text rewrites these passages with the intent of revealing to the reader these covenantal references only hinted at in the Bible.